Annual variations in GPS‐measured vertical displacements near Upernavik Isstrøm (Greenland) and contributions from surface mass loading. Issue 1 (26th January 2017) - Liu, Lin; Khan, Shfaqat Abbas; van Dam, Tonie; Ma, Joseph Ho Yin; Bevis, Michael
Abstract: In response to present‐day ice mass loss on and near the Greenland Ice Sheet, steady crustal uplifts have been observed from the network of Global Positioning System (GPS) stations mounted on bedrock. In addition to the secular uplift trends, the GPS time series also show prominent annual variability. Here we examine the annual changes of the vertical displacements measured at two GPS stations (SRMP and UPVK) near Upernavik Isstrøm in western Greenland. We model elastic loading displacements due to various surface mass loading including three nonice components: atmospheric pressure, ocean bottom pressure, continental water storage, and one ice component, i.e., surface mass balance (SMB). We find that the contribution from atmospheric pressure changes can explain 46% and 78% of the annual amplitude observed in the GPS verticals at SRMP and UPVK, respectively. We also show that removing the predicted loading displacements due to SMB adversely increases the annual variance of the GPS residuals. However, using the GPS data alone, we cannot identify the exact cause(s) of this discrepancy because the annual loading displacements are sensitive to the SMB changes from over 85% of the ice sheet area. Alternatively, by differencing vertical displacements between the two stations, we find a good agreement between the modeled differential SMB loading displacements and the GPS residuals after removing nonice components. Our study highlights the necessity of correcting for nonice loading contributions in the GPS measurements of crustal deformation to infer ice mass changes in Greenland at annual periods. Key Points: Atmospheric pressure loading contributes to half of the GPS vertical displacements at annual periods Annual verticals are sensitive to ice mass balance over 85% of the entire ice sheet Differential verticals between stations are useful to constrain ice mass changes within 120 km